Rhinoxenus bulbovaginatus (Monogenea, Dactylogyridae) parasite of the nasal cavities of Salminus hilarii (Characiformes, Characidae) in a Neotropical River, SP, Brazil - Narciso, Rodrigo Bravin [UNESP]; Brandão, Heleno; Yamada, Fábio Hideki [UNESP]; Silva, Reinaldo José da [UNESP] (My University, 2013)
The aim of study is to report for the first time the occurrence of Rhinoxenus bulbovaginatus infesting the nasal cavity of Salminus hilarii from the Taquari River, São Paulo State, Brazil. Rhinoxenus bulbovaginatus was originally described parasitizing the nasal cavities of Salminus brasiliensis from the Paraná River. Rhinoxenus spp. are monogenean parasites from the nasal cavities of Characiformes fishes in the Neotropical region. To date, eight species of Rhinoxenus were described in seven different hosts. This study broadens the range of hosts parasitized with monogeneans of nasal cavities.

El objetivo del trabajo es registrar una nueva ocurrencia de Rhinoxenus bulbovaginatus en la cavidad nasal de Salminus hilarii del río Taquari, Estado de São Paulo, Brasil. Rhinoxenus bulbovaginatus fue originalmente descrita parasitando cavidades nasales en Salminus brasiliensis del río Paraná. Rhinoxenus spp. son monogéneos parásitos de las cavidades nasales de los peces Characiformes en la región Neotropical. Hasta la fecha, ocho especies de Rhinoxenus fueron descritas en siete especies hospederas. El presente estudio amplía el rango de hospederos parasitados con monogéneos de las cavidades nasales.
Rhinoxenus bulbovaginatus (Monogenea, Dactylogyridae) parásito de la cavidad nasal de Salminus hilarii (Characiformes, Characidae) en una río neotropical, SP, Brasil
Keywords: Ancyrocephalinae; Freshwater fish; Neotropical region; Tabarana; Ancyrocephalinae; Peces de agua dulce; Neotropicales; Tabarana